A comparison of two online cognitive‐behavioural interventions for symptoms of depression in a student population: The role of therapist responsiveness. Issue 3 (16th August 2013) - Richards, Derek; Timulak, Ladislav; Hevey, David
Abstract: Objectives : The study aimed to compare the efficacy of eight weekly sessions of a self‐administered online CBT treatment (cCBT; n =51) to a therapist‐assisted email CBT treatment (eCBT; n =50) in University students. Design : The design was a randomised parallel group trial. The study randomised participants with symptoms of depression to one of two available treatments. Method : Participants were offered eight weekly sessions of either cCBT or eCBT. Participants completed the Beck Depression Inventory‐II (BDI‐II) and the Clinical Outcomes in Routine Evaluation – Outcome Measure (CORE‐OM) at pre‐and post‐treatment, at weeks 16 and 32 follow‐up. The Working Alliance Inventory‐Short Form (WAI‐SR) was completed at weeks 2, 4, and 6. Results : For both groups, pre‐post within group effect sizes reported were large for the BDI‐II and the CORE‐OM and these were maintained at follow‐up. Perceptions of working alliance were similar in each group, but Bond was significantly stronger for the eCBT condition. WAI scores correlated more positively with the outcome on BDI‐II for those in the eCBT condition than the cCBT condition, but not significantly. Conclusion : There were no significant differences between the two online treatments, both reduced depressive symptoms and improved general functioning. Similarly, at post‐treatment and follow‐up, clinical improvement and recovery was demonstrated for both groups equally. The study demonstrates the possibility for cCBT in a university setting that may contribute to addressing the shortcomings in meeting increasing demands that mental health services presently face.